Concentration of Sindbis virus with optimized gradient insulator-based dielectrophoresis. Issue 6 (15th February 2016) - Ding, Jie; Lawrence, Robert M.; Jones, Paul V.; Hogue, Brenda G.; Hayes, Mark A.
Abstract : Rapid concentration of Sindbis virus using optimized gradient insulator-based Dielectrophoresis (i-gDEP). Abstract : Biotechnology, separation science, and clinical research are impacted by microfluidic devices. Separation and manipulation of bioparticles such as DNA, protein and viruses are performed on these platforms. Microfluidic systems provide many attractive features, including small sample size, rapid detection, high sensitivity and short processing time. Dielectrophoresis (DEP) and electrophoresis are especially well suited to microscale bioparticle control and have been demonstrated in many formats. In this work, an optimized gradient insulator-based DEP device was utilized for concentration of Sindbis virus, an animal virus with a diameter of 68 nm. Within only a few seconds, the concentration of Sindbis virus can be increased by two to six times in the channel under easily accessible voltages as low as about 70 V. Compared with traditional diagnostic methods used in virology, DEP-based microfluidics can enable faster isolation, detection and concentration of viruses in a single step within a short time.